Elvis Presley goes into the Army (Module II, 2013)
USA. Tennessee, Memphis. Elvis Presley chatting with a young woman and his mother Galdys Presley (not heard).Footage of Elvis signing a form and being fingerprinted by an army official.Presley signs autographs and poses with record sleeve of new album.Shot of Kennedy Veteran's Hospital building sign, "Examining and Induction Station".Shot of the sign, "Insignia of the Third Army" as Elvis stands underneath eating an apple and laughing.Elvis sitting with other recruits listening to induction speech.